A construção de significados sobre letramento e seus recentes estudos durante a formação inicial e contínua de professores de língua estrangeira - Jesus, Deborah Nathalia Silva de (Universidade Federal de São Carlos, 2012)
The contemporary period is marked by technological development and by economic, political, cultural and social changes influenced by globalization. Such changes had its impact on Brazilian education, encouraging researches and new proposals for education, in order to adapt it to new goals and needs of society. It is intended to leave behind teaching practices based on a banking model of education and to introduce new concepts and technologies, such as literacy and its more recent studies, such as multiliteracies, new literacies and critical literacy. The school has the responsibility of forming critical citizens, prepared for social and political interaction and for new demands of labor market. Meanwhile, teachers must be updated to understand, discuss and work in the classroom with the new guidelines for education, as well as to reflect about their practice. Foreign language teachers, especially of English, the language of globalization, have also the challenge of affirming the social and educational role of their discipline. This research is interested, therefore, in understanding how knowledge about educational theories is constructed by English teachers in initial or continuous formation. The concern with the theoretical knowledge construction by teachers is justified by its importance for the development of an informed and conscious practice, in which the teacher can explain the process of teaching, analyze it and, above all, transform it.
Keywords: Linguística; Letramento; Professores - formação; Língua estrangeira; Documentos oficiais para a educação; Literacy and its recent studies; Official guidelines for education; Theoretical formation of language teachers; LINGUISTICA, LETRAS E ARTES::LINGUISTICA